Myocardial fibrosis by late gadolinium enhancement cardiac magnetic resonance and hepatitis C virus infection in thalassemia major patients. Issue 10 (October 2015) - Pepe, Alessia; Meloni, Antonella; Borsellino, Zelia; Cuccia, Liana; Borgna-Pignatti, Caterina; Maggio, Aurelio; Restaino, Gennaro; Gagliardotto, Francesco; Caruso, Vincenzo; Spasiano, Anna; Filosa, Aldo; Centra, Michele; et al.
<x xml:space="preserve">Abstract</x> Aims Our aim was to evaluate the correlation between myocardial fibrosis detected using the late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) technique and chronic hepatitis C (CHC) in a large, retrospective, multicentre cohort of thalassemia major patients. Methods LGE images were acquired in 434 thalassemia major patients (233 men, 31 ± 9 years) enrolled in the MIOT (Myocardial Iron Overload in Thalassemia) study. Hepatitis C virus (HCV)-RNA tests were sensitive to detect more than 50 copies/ml. Results No patient manifested moderate/severe adverse events associated with the use of Gadobutrol. Myocardial fibrosis was detected in 90 (21%) patients. Among the 312 patients tested for HCV-RNA, there was a significant correlation between the presence of myocardial fibrosis and CHC (P = 0.011). Among the 62 patients with myocardial fibrosis tested for HCV-RNA, we found a significantly higher prevalence of diabetes mellitus in CHC patients versus the no-CHC patients (P = 0.049). Conclusion Our findings support the use of the LGE CMR approach well tolerated in the thalassemia major patients with CHC. HCV infection can be involved in the pathogenesis of myocardial fibrosis through both myocarditis directly and the pancreas and liver damage with the development of diabetes indirectly. These patients could therefore benefit from cardioactive drugs and therapeutic interventions directed towards the eradication of virus.